38 - REFLECTIONS ON THE BODY AND ITS HISTORICAL DEVELOPMENT (Fiep Bulletin - online, 2021)
Abstract: The aim of this article is to present a reflection on the representations of the body throughout history. For this, we rely on the works of Michel Foucault (2005), Richard Sennett (2016), David Le Breton (2007), Lipovetsky (2005) and other authors who bring contributions on this theme. The body will not be taken as a finished and defined form, but as an element in constant change that tends to vary according to the historical needs that constitute it. Thus, we propose to think about some social and cultural aspects, which have contributed to the construction of the body in our society throughout history.